Problemy psichologii sporta - Rodionov, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The psychology of sports is the branch of psychological science studying the features of a person, working in the specific conditions of sports activity and thus appearing in specific mental conditions.